2020
DOI: 10.1155/2020/8880045
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Ferritin Is Superior over Soluble Transferrin Receptor and Hepcidin in Predicting Anemia in the Third Trimester: Result from a Cohort Study in Indonesia

Abstract: Introduction. Anemia in the third trimester has been identified as a risk factor for maternal and fetal morbidity that might lead to mortality. Due to its high cost, finding the best marker to predict anemia became more important to allow early prevention. Only one of ferritin, hepcidin, or soluble transferrin receptors can be picked for the prediction of anemia in the third trimester especially in low-resource setting. Objective. This study aimed at defining the best marker among ferritin, hepcidin, or solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The mechanisms of transport of these proteins from the future mother to the fetus and their origin in meconium are unclear. Several studies have demonstrated the usefulness of measuring ferritin concentrations in pregnant women's serum as a factor in predicting anemia [21,22]; therefore, a comparison of these results with the determination of ferritin in newborn meconium may provide additional knowledge in explaining the connections between mother and fetus.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of transport of these proteins from the future mother to the fetus and their origin in meconium are unclear. Several studies have demonstrated the usefulness of measuring ferritin concentrations in pregnant women's serum as a factor in predicting anemia [21,22]; therefore, a comparison of these results with the determination of ferritin in newborn meconium may provide additional knowledge in explaining the connections between mother and fetus.…”
Section: Discussionmentioning
confidence: 99%